Description of Pseudosteineria longisetis sp. n. from northeastern Brazil with a review of the genus Pseudosteineria Wieser, 1956 (Nematoda: Xyalidae) - Cidreira, Gabriel; Venekey, Virág; de Souza Alves, Orane F.; Kelmo, Francisco (Zootaxa, 2020)
A new free-living marine nematode of the family Xyalidae is described from Armação Beach, northeastern Brazil, and the genus Pseudosteineria is reviewed. Pseudosteineria longisetis sp. n. is characterized by having six groups of long subcephalic setae, amphids situated slightly anterior to the groups of subcephalic setae or at the level of the first subcephalic setae, long somatic setae located posteriorly to subcephalic setae and distributed along the body, one papiliform precloacal supplement, and gubernaculum with dorso-caudal apophysis. An emended diagnosis of the genus, an updated list of species and dichotomous identification key, and a pictorial key are given. A comparative table including the main characters of all Pseudosteineria species is also provided.